If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 2b + c = 8 Solving 4a + 2b + c = 8 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2b' to each side of the equation. 4a + 2b + -2b + c = 8 + -2b Combine like terms: 2b + -2b = 0 4a + 0 + c = 8 + -2b 4a + c = 8 + -2b Add '-1c' to each side of the equation. 4a + c + -1c = 8 + -2b + -1c Combine like terms: c + -1c = 0 4a + 0 = 8 + -2b + -1c 4a = 8 + -2b + -1c Divide each side by '4'. a = 2 + -0.5b + -0.25c Simplifying a = 2 + -0.5b + -0.25c
| 12-4(6x-2)=8-(2x+5) | | 35=5u | | 2x+6=7-3x | | 97=215t+-16t^2 | | y=sin(5x+2) | | 7w-16w= | | 6c=4c+6 | | 5(k-3)-8=5k-(4k-3) | | 4x+3-5x= | | 2x+80+145+x=360 | | -8g+4.5=36.3 | | 0.2(1.4-3x)+1.3x-2.9= | | c-d-5c+d= | | -3x-4=2(7x-4) | | 5+bx+3x=11 | | 9d^3=25 | | g(x)=-4x(x^2-16)(x-5) | | 11-4+8=4x+10 | | 2.91=24.444 | | 5x-6+2x=120 | | 5X(X+1)=2X+17 | | 5x+(x+1)=2X+17 | | 4u=25-3z | | 4-6cosx=8-2cosx | | 3x-6=4a+2x | | 3x(8-2)+4x-3= | | 4d+8=64 | | 5w-9=-74 | | -5q+4+6q-13=5-4(3q-4)+2q | | 8(x+3)-22= | | 17x-6(9-2x)=21-(7x+15) | | 7(2x+5y)+xy-6(3xy+5y)= |